The effects of hemolysis on plasma prothrombin time and activated partial thromboplastin time tests using photo-optical method. Issue 38 (September 2017) - Hernaningsih, Yetti; Akualing, Jeine Stela
Abstract : Abstract: Hemolysis is the most common reason why coagulation test samples are rejected. However, the effects of hemolysis on plasma prothrombin time (PPT) and activated partial thromboplastin time (APTT) are rarely investigated and the results are controversial. This research aims to analyze the effects of hemolysis on PPT and APPT using the photo-optical method. Nonhemolyzed citrate blood samples (n = 30) with normal PPT and APTT underwent 2-step mechanical lysis and then hemoglobin level measurement was carried out at each step. The first lysis was mild to moderate resulting in a hemoglobin level of <0.8 g/dL. These samples were labeled as group 1. The second step showed more severe lysis, which resulted in a plasma hemoglobin level of ≥0.8 g/dL. These samples were labeled as group 2. Analysis was carried out on the PPT and APTT differences between the 2 groups and baseline, as well as between group 1 and group 2 using repeated-measures analysis of variance (ANOVA). The effects of hemolysis were analyzed using linear regression. Receiver operating characteristic (ROC) curve analysis was performed to determine the cut-off value in PPT and APTT. Significantly shorter APTT was measured for group 1 than baseline, ( P = .000), group 2 than baseline ( P = .000), and group 2 than group 1 ( P = .003). With regard to PPT results, those for group 1 were significant shorter than baseline ( P = .002), while those for group 2 were significantly longer than group 1 ( P = .000). In the correlation assay, the level of hemolysis revealed a mildly significant correlation to APTT ( R = 0.245; P = .02). Cut-off value for PPT was 1.55 g/dL (100% sensitivity and 87.9% specificity), while the value for APTT was 0.95 g/dL (75% sensitivity and 62.5% specificity). Not all hemolyzed samples should be rejected for PPT and APTT tests using photo-optical methods.